Toward ultraflexible organic electronic devices - Park, Sungjun; Takakuwa, Masahito; Fukuda, Kenjiro; Lee, Sunghoon; Yokota, Tomoyuki; Someya, Takao (MRS Bulletin, 2023)
In recent decades, organic electronics have progressed remarkably, owing to their exceptional mechanical and electrical properties. The development of ultraflexible organic electronics has opened up possibilities for applications such as wearable electronics, flexible displays, and skin- and tissue-compatible sensors with good breathability. In this article, we introduce state-of-the-art ultrathin and high-performance functional organic electronic devices and their integration with potential applications. Our focus is on the strategies for advancing new materials, novel device structures, and diverse applications, which have enabled the development of multifunctional and complex systems. Additionally, we highlight the challenges and opportunities for future research in this field, including improving stability and reliability over long periods, ensuring scalability and cost-effectiveness of production, and addressing issues related to integration into larger systems. Finally, we present future directions in this exciting and rapidly growing field of ultraflexible organic electronics. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Breathability; Devices integration; Mechanical and electrical properties; OLED; OPD; OPV; Organic electronic devices; Organic electronics; OTFT; Ultraflexible electronic; Device integration; OLEDs; OPDs; OPV; OTFTs; Ultraflexible electronics